2018
DOI: 10.3390/cryst8030115
|View full text |Cite
|
Sign up to set email alerts
|

Design of Spin-Frustrated Monomer-Type C60•− Mott Insulator

Abstract: Spin-frustrated monomer-type Mott insulator C 60•− solids are discussed in this review article. For the C 60 •− solids, the interfullerene center-to-center distance (r) is the key parameter that controls the competition between covalent bond-formation, itinerancy, and spin frustration. Eight C 60•− salts with various compositions and dimensionalities are reviewed. In all of these C 60 •− salts except one, neither bond-formation nor long-range magnetic ordering was observed down to low temperatures. A plot of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 167 publications
0
13
0
Order By: Relevance
“…60 is a radical anion) [50], in which one can clearly identify corner-sharing trigonal bipyramidal clusters. Although the mentioned compounds do not represent a precise experimental realization of the magnetic structure proposed in the present paper, we hope that a targeted design of the magnetic material with a magnetic structure of interconnected trigonal bipyramids is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…60 is a radical anion) [50], in which one can clearly identify corner-sharing trigonal bipyramidal clusters. Although the mentioned compounds do not represent a precise experimental realization of the magnetic structure proposed in the present paper, we hope that a targeted design of the magnetic material with a magnetic structure of interconnected trigonal bipyramids is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Additionally, Yamada et al observed a triplet chargeseparated state by laser-exciting a curved -surface donor and Li + @C60 in solution. 3 Although C60 is an ideal ligand to realise topological architectures owing to its isotropic coordination environment, 22 to date, no candidates have been reported for the experimental realisation of electrically conductive and magnetically frustrated solids based on Li + @C60. On the other hand, the S = ½ electronic system holds promise for exploring interesting quantum phenomena such as unconventional superconductivity [23][24][25][26] and quantum spin liquids (QSLs) which are commonly observed in triangular or kagomé lattices.…”
Section: Introductionmentioning
confidence: 99%
“…Highly symmetric C 60 exhibits complex Jahn‐Teller (JT) dynamics characterized by orbital‐vibration entanglement in various charged and excited states . Negatively charged C 60 has been one of the most investigated cases because it forms various molecular crystals . Since the molecular nature strongly remains in these materials, thorough understanding of the JT effect of C 60 anions is crucial.…”
Section: Introductionmentioning
confidence: 99%